At the threshold of viability: to resuscitate or not to resuscitate - the perspectives of Israeli neonatologists - Daniel Sperling; Liron Borenstein-Levin; Ori Hochwald; Arieh Riskin (BMJ Publishing Group, 2024)
Objective This study aims to examine the perspectives of neonatologists in Israel regarding resuscitation of preterm infants born at 22-24 weeks gestation and their consideration of parental preferences. The factors that influence physicians' decisions on the verge of viability were investigated, and the extent to which their decisions align with the national clinical guidelines were determined.Study design Descriptive and correlative study using a 47-questions online questionnaire.Results 90 (71%) of 127 active neonatologists in Israel responded. 74%, 50% and 16% of the respondents believed that resuscitation and full treatment at birth are against the best interests of infants born at 22, 23 and 24 weeks gestation, respectively. Respondents' decisions regarding resuscitation of extremely preterm infants showed significant variation and were consistently in disagreement with either the national clinical guidelines or the perception of what is in the best interest of these newborns. Gender, experience, country of birth and the level of religiosity were all associated with respondents' preferences regarding treatment decisions. Personal values and concerns about legal issues were also believed to affect decision-making.Conclusion Significant variation was observed among Israeli neonatologists regarding delivery room management of extremely premature infants born at 22-24 weeks gestation, usually with a notable emphasis on respecting parents' wishes. The current national guidelines do not fully encompass the wide range of approaches. The country's guidelines should reflect the existing range of opinions, possibly through a broad survey of caregivers before setting the guidelines and recommendations.